2011
DOI: 10.1111/j.1542-4758.2011.00547.x
|View full text |Cite
|
Sign up to set email alerts
|

Statin use is associated with lower inflammation and erythropoietin responsiveness index in hemodialysis patients

Abstract: Patients with end-stage renal disease are prone to inflammation and inflammation is related to erythropoietin-stimulating agent hyporesponsiveness and mortality in this population. Statins have been demonstrated to reduce cardiovascular mortality in selected populations of end-stage renal disease patients. These drugs have pleiotrophic effects such as anti-inflammation. In this retrospective analysis, we determined whether the use of statins improves inflammation and inflammation-related anemia in a cohort of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…Despite being a nutritional status index, related to protein intake, its higher levels can also correlate with lower urinary losses, as it is an attributable beneficial effect of statins. 7,20 Statins seem to have a synergic effect with erythropoiesis stimulating agents (ESA) lowering their consumption, in accordance to the Koc M et al, 25 study result. In fact in our population, there were no differences in hemoglobin levels, but it was due to higher dosages of ESA in the group without statins prescription.…”
Section: Discussionsupporting
confidence: 71%
“…Despite being a nutritional status index, related to protein intake, its higher levels can also correlate with lower urinary losses, as it is an attributable beneficial effect of statins. 7,20 Statins seem to have a synergic effect with erythropoiesis stimulating agents (ESA) lowering their consumption, in accordance to the Koc M et al, 25 study result. In fact in our population, there were no differences in hemoglobin levels, but it was due to higher dosages of ESA in the group without statins prescription.…”
Section: Discussionsupporting
confidence: 71%
“…Other studies have consistently demonstrated a mechanistic link between chronic inflammation and ESA hyporesponsiveness, highlighting the association between increased inflammatory markers and a reduced response to ESA therapy. [1619] In contrast, we did not observe an association between increased hs-CRP levels and ESA hyporesponsiveness as reported in other studies. [18,19] Reasons for this are not clear but may be explained, in part, by the timing of these measures, as baseline hs-CRP levels for statin users were taken and recorded after initiating statin treatment.…”
Section: Discussionsupporting
confidence: 56%
“… 9 For example, statin treatment inhibits the progression of aneurysms associated with degenerative atherosclerosis 33 and diminishes inflammation and related anemia in end-stage renal disease. 34 McKay et al 18 were among the earliest investigators to suggest the possibility of simvastatin for the treatment of allergic airway disease.…”
Section: Discussionmentioning
confidence: 99%